Map men transnational lives and deaths of geographers in the making of East Central Europe - Seegel, Steven (The University of Chicago Press, 2018)
"This book is a group intellectual biography of five prominent geographers from East Central Europe and the United States between the 1870s and the 1950s. Seegel recreates the public and private worlds of these mapmakers, who interacted with and influenced one another even as they played key roles in defining and redefining borders, territories, nations, and ultimately the interconnection of the world throughout the period that includes the two World Wars."--Provided by publisher.